Development and validation of a short tool to assess the awareness of hypertensive disorders of pregnancy: a cross-sectional study among pregnant women in LebanonAJOG Global Reports at a Glance - Jinan Kresht, MS; Georges Hatem, PhD; Nathalie Lahoud, PhD; Salam Zein, PhD; Dalia Khachman, PhD (Elsevier, 2023)
BACKGROUND: Hypertensive disorders of pregnancy (HDPs) are responsible for most perinatal and fetal mortality. Few programs are patient-centered during pregnancy, thereby increasing the risks of misinformation and misconceptions among pregnant women and, as a result, malpractices. OBJECTIVE: This study aims to develop and validate a form to assess the knowledge and attitudes of pregnant women about HDPs. STUDY DESIGN: A cross-sectional pilot study was conducted over 4 months, targeting 135 pregnant women from 5 obstetrics and gynecology clinics. A self-reported survey was developed and validated, and an awareness score was generated. RESULTS: The mean maternal age of the participants was 27.3 (5.3) years. About 80% of the participants reported that they monitored their weight during pregnancy, and 70.4% monitored their blood pressure, out of which 73.8% performed it at the doctor's clinic only. Overall, participants had a total score of 16.9 (3.1) over 25 with higher attitude scores than knowledge scores. Less than half of the patients (45.2%) knew the cut-off for hypertension. With respect to knowledge statements, higher scores were noted for statements related to the symptoms of HDPs, and lower scores were reported for statements related to some HDP complications. Older women and those who monitored their blood pressure during pregnancy had significantly higher awareness scores. Those working had higher awareness of HDPs (67.4%), whereas about half of nonworkers (53.9%) showed lower awareness scores (P=.019). CONCLUSION: Pregnant women had moderate awareness of HDPs. The short 25-item tool developed in the present study can be used in obstetric clinics to explore the awareness of women of HDPs.